Trichoderma asperellum efficiently protects Quercus robur leaves against Erysiphe alphitoides - Tomasz Oszako; Dmitry Voitka; Marcin Stocki; Natalia Stocka; Justyna Anna Nowakowska; Anna Linkiewicz; Tom Hsiang; Lassaâd Belbahri; Daria Berezovska; Tadeusz Malewski (European Journal of Plant Pathology, 2021)
The protective effects of Trichoderma asperellum IZR D-11 as a biocontrol agent against the powdery mildew Erysiphe alphitoides infecting leaves of Quercus robur were evaluated for the first time. A strain of Trichoderma had earlier been isolated in Belarus, and was identified in this study as T. asperellum by sequencing of three genomic markers: internal transcribed spacer, translation elongation factor 1 alpha and RNA polymerase II subunit 2, with over 99.2% identity to corresponding genomic sequences in GenBank. When applied once in the first year just after onset of powdery mildew disease, T asperellum IZR D-11 reduced disease progression and continued to reduce powdery mildew levels during the following three years. Photosynthetic activity as represented by chlorophyll fluorescence measured in oak seedlings was increased in treated plants, and greater assimilate production was also found. The use of this antagonistic fungus increased the total water content in oak leaves suggesting that T. asperellum IZR D-11 can serve as a preventive measure to reduce energy losses in the process of water transpiration. GC-MS analysis detected 49 volatile compounds in the headspace of pure cultures of T. asperellum . Sesquiterpenes represented mainly by daucene, dauca-4(11),8-diene and isodaucene were the largest group of compounds emitted. We speculate that these volatiles from T. asperellum IZR D-11 may be involved in induced resistance in the plant, but further research is needed. The above results suggest that T. asperellum strain IZR D-11 has potential as a biocontrol agent of oak powdery mildew in forest nurseries.